2018
DOI: 10.3389/fncel.2018.00144
|View full text |Cite
|
Sign up to set email alerts
|

Physical Biology of Axonal Damage

Abstract: Excessive physical impacts to the head have direct implications on the structural integrity at the axonal level. Increasing evidence suggests that tau, an intrinsically disordered protein that stabilizes axonal microtubules, plays a critical role in the physical biology of axonal injury. However, the precise mechanisms of axonal damage remain incompletely understood. Here we propose a biophysical model of the axon to correlate the dynamic behavior of individual tau proteins under external physical forces to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 84 publications
1
31
1
Order By: Relevance
“…1) [22] and delineating the contributions of the different components is not trivial. It has been generally assumed that bundled microtubules are the main mechanical element in axons [23,24]. However, our results demonstrate that Factin and spetcrin play a very prominent role in axonal mechanical response.…”
Section: Folding-unfolding Of Spectrin Buffers Axon Tensioncontrasting
confidence: 53%
See 2 more Smart Citations
“…1) [22] and delineating the contributions of the different components is not trivial. It has been generally assumed that bundled microtubules are the main mechanical element in axons [23,24]. However, our results demonstrate that Factin and spetcrin play a very prominent role in axonal mechanical response.…”
Section: Folding-unfolding Of Spectrin Buffers Axon Tensioncontrasting
confidence: 53%
“…Hence, the effects of microtubule perturbation, for instance, may be more complex than a simple change in their numbers. Microtubule bundles alone can account for softening if their cross-linkers (MAPs) exhibit binding-unbinding dynamics, but such models give a long time fluid like response [23,24] and also cannot account for the peak in the relaxation time vs strain plot. Thus, while microtubules may be making a direct contribution to the effective moduli we measure, microtubule elasticity alone cannot account for the entire set of experimental observations we report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4147 More recently, FE models of the axon have been proposed to shed a light on the mechanism behind axonal injury. 25,26,4850…”
Section: Methodsmentioning
confidence: 99%
“…18,19 These studies have further motivated the development of models (both analytical and computational) having the microtubule bundle as a focus. 2025 In our previous work, however, we have shown with a finite element model of the entire axon that, especially when including detachment of tau protein elements, deformations in the microtubules did not pass the suggested microtubule failure thresholds. 26 On the contrary, we found that, as a result of axonal stretching and of microtubules distancing, very high strain localization formed on the axonal membrane.…”
Section: Introductionmentioning
confidence: 91%